Chapter 6 Ordering Human-Other Relationships International Humanitarian Law and Ecologies of Armed Conflicts in the Anthropocene - Arvidsson, Matilda (Taylor & Francis, 2023)
This chapter analyses the international humanitarian legal ordering of human and other relationships during armed conflict and disaster by looking at two examples, namely the 'natural' environment and human-scientific constructed AI-powered swarms of drones. Drawing on these examples, as well as post-anthropocentric and posthuman legal scholarship, the authors argue that International Humanitarian Law (IHL) has some potential in developing in a post-anthropocentric direction, specifically in reorienting its focus from armed conflicts to violent outbursts by making use of the Deleuze-Guattarian notion of 'war-machines'. The authors argue that this will enable IHL to offer a better protection on a less anthropocentric and more inclusive and equal basis in a shared posthuman ecology. The chapter offers an overview of current legal regulations as well as a theoretical and practice-oriented outline for the development of IHL.